Removal and degradation of the fungicide dye malachite green from aqueous solution using the system wheat bran–Fomes sclerodermeus - Papinutti, Víctor Leandro (2006)
The triphenylmethane dye malachite green (MG), commonly used as fungicide, was adsorbed onto wheat bran (WB) by using a batch technique. The effects of contact time, dye concentration and pH were investigated. The equilibrium was attained after 40 min of contact time irrespective of MG concentration. The pH of MG aqueous solution greatly influenced the adsorption capacity and intensity, it was found that maximum adsorption of dye occurred at pH range 7–9, where the amount of dye removed was nearly 90%. Data obtained on adsorption at different dye concentrations and pH range 4–7 were used to plot the Freundlich isotherms. WB with MG adsorbed at pH range 4–7 was used as substrate for the growth of the white rot fungi Fomes sclerodermeus and Phanerochaete chrysosporium. The presence of MG (nearly 24 mg g−1 dry WB) delayed the fungal growth. MG was completely degraded by F. sclerodermeus cultures at pH 5, in concordance with the highest ligninases production. Thus, pH values not only influenced the adsorption capacity of WB but they were also important for growth, enzyme production and finally, dye degradation. This technique should have broad applications in bioremediation processes of water and wastewater.